OHS Work Procedure Implementation and CSMS Performance in Construction Projects - Adriana Karundeng; Ahmad Yani Abas; Cyntha Tendean; Fandel Maluw; Floren Agnesia Sinaga (Jurnal Ilmiah Teknik, 2026)
High accident risk in construction projects indicates that OHS documentation alone is insufficient without consistent on-site implementation of safe work procedures. Objective: This study evaluates the implementation of Occupational Health and Safety (OHS) based work procedures and analyzes their impact on the performance of the Construction Safety Management System (CSMS) in the Architectural Christian Center construction project, addressing the gap between administrative and operational compliance. Methodology: An evaluative design with combined descriptive quantitative and qualitative approaches was applied. Data were collected through questionnaires administered to project personnel, field observations, and reviews of OHS-related documents. Analysis compared on-site practices with applicable regulations and the CSMS theoretical framework, supported by interpretation of questionnaire and observation results to identify implementation gaps. Findings: Normatively, OHS-based work procedures meet CSMS documentation requirements; however, operational implementation remains ineffective. Work procedures and Job Safety Analysis (JSA) are still treated primarily as administrative instruments and are not consistently integrated into daily work execution methods. Worker compliance is uneven: PPE use shows relatively better adherence than compliance with work procedures and JSA, indicating that risk control is still oriented toward individual protection rather than optimized through administrative controls and engineering-based work methods. Additionally, positioning OHS personnel within the contractor’s internal organization may reduce the independence and effectiveness of safety supervision due to pressures related to time, cost, and progress targets. Implications: Improving CSMS performance requires stronger integration of work procedures and JSA into routine execution, more consistent enforcement of procedural compliance, and strengthened supervisory authority to reduce reliance on PPE. Originality: This study explicitly links OHS work procedure implementation to CSMS performance while highlighting the contractor-internal OHS organizational structure as a structural factor affecting enforcement effectiveness, and provides actionable recommendations to embed safety within engineering-based construction execution methods.